Financial Savvy or Lifestyle Driven? Investigating The Spending Patterns of Bank Indonesia Scholarship Recipients - Rizki Febri Eka Pradani; Nurul Ulfa Qomariyah (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2025)
This study explores how lifestyle and financial literacy on the spending behavior of students receiving bank indonesia scholarships at nurul jadid university. This study aims to address existing gaps and highlight differences from previous research by focusing on students who receive financial support from external sources. Quantitative methods are applied in this study with an emphasis on associative approach, the research population was 50 student who received the Bank Indonesia Scholarship at Nurul Jadid University for the 2024 period, which was also sampled through saturated sampling technique. Data were obtained through questionnaires and processed using validity, reliability, coefficient of determination, multiple linear regression, as well as T test and F test. The findings of the study indicate that, individually, lifestyle has a positive and significant influence on students' spending behavior, whereas financial literacy shows a negative but insignificant impact. However, when considered together, both lifestyle and financial literacy possess a positive and significant impact on the spending behavior of students who receive Bank Indonesia scholarships at Nurul Jadid University.Keywords: Lifestyle, Financial Literacy, Spending Behavior